2016
DOI: 10.1177/0734371x16658334
|View full text |Cite
|
Sign up to set email alerts
|

Person–Organization Fit and Turnover Intention: Exploring the Mediating Role of Employee Followership and Job Satisfaction Through Conservation of Resources Theory

Abstract: This study examines the mediating role of employee followership and job satisfaction in the relationship between person–organization (P-O) fit and turnover intention. Understanding the mechanisms that link P-O fit and turnover intention may provide useful intervention strategies for leaders and human resource professionals to effectively manage and interact with their followers. Using Hobfoll’s conservation of resources theory, we explore a three-step mediation model in which high P-O fit is related to turnove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
144
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(152 citation statements)
references
References 81 publications
(129 reference statements)
8
144
0
Order By: Relevance
“…Besides, new recruits with similar values to those of an organization are more satisfied with the job and more likely to stay with the organization longer (Chatman, 1991). More recent studies have further substantiated the benefits of high of level of POF for employees performance (Hamstra et al, 2018), organization commitment (Kooij and Boon, 2018), job satisfaction (Jin et al, 2018), and strengthening the membership of the employees with the organization (Boon and Biron, 2016). Finally, the attrition stage of the ASA model suggests that employees who do not fit the organisations are more likely to think of leaving the job.…”
Section: Person-organization Fit and The Intention To Leavementioning
confidence: 95%
“…Besides, new recruits with similar values to those of an organization are more satisfied with the job and more likely to stay with the organization longer (Chatman, 1991). More recent studies have further substantiated the benefits of high of level of POF for employees performance (Hamstra et al, 2018), organization commitment (Kooij and Boon, 2018), job satisfaction (Jin et al, 2018), and strengthening the membership of the employees with the organization (Boon and Biron, 2016). Finally, the attrition stage of the ASA model suggests that employees who do not fit the organisations are more likely to think of leaving the job.…”
Section: Person-organization Fit and The Intention To Leavementioning
confidence: 95%
“…Apart from values, person-organization fit includes the compatibility between employees' and organization's goals. If there are many incompatibilities between employees' characteristics and organizational values and goals, then employees are more likely to have turnover intention (Jin, McDonald, & Park, 2016). Numerous studies (O'Reilly, Chatman, & Caldwell, 1991;Kristof, 1996;Kristof-Brown, Zimmerman, & Johnson, 2005) indicate that personorganization fit is associated with turnover.…”
Section: Kata Kunci: Job Embeddedness Person-organization Fit Turnomentioning
confidence: 99%
“…The concept of person-organization fit was developed from Schneider's (1987) attraction-selection-attrition (ASA) model and the social exchange theory (Blau, as cited in Jin et al, 2016). ASA contain perspectives, which can build high person-organization fit in an organization.…”
Section: Person-organization Fitmentioning
confidence: 99%
“…Secondly, a considerable number of studies have shown that job satisfaction is negatively related to turnover intentions [34]. Job satisfaction is generally considered a multifaceted construct that includes pay, promotion opportunities, coworkers, supervision, and the work itself [35].…”
Section: Job Embeddedness Job Satisfaction Affective Commitment Andmentioning
confidence: 99%
“…Previous research indicates that employee demographic characteristics (e.g., gender, age, salary) and structural variables (number of staffs, corporate tenure) have a noticeable influence on turnover intentions (e.g., [34,56]). Therefore, this study treated the following variables as control variables: employee age, employee salary, number of people in the venture, and corporate tenure.…”
Section: Control Variablesmentioning
confidence: 99%